Evaluation of software for mental health promotion of undergraduate nursing students in the early years of college - Baldassarini, Caíque Rossi; Gonçalves, Jamila Souza; Masella, Tania Aparecida Cancian; Oliveira, Jaqueline Lemos de; Souza, Jacqueline de (Revista da Escola de Enfermagem da USP, 2022)
Objective: To evaluate mental health promotion software for students in the early years of undergraduate nursing course. Method: Descriptive study developed with 41 undergraduates from a private higher education institution in an inland city of the state of São Paulo, approved by the Research Ethics Committee. Data collection was carried out remotely from April to October 2021, using a sociodemographic characterization questionnaire and student assessment of the software. The results were analyzed by descriptive statistics. Results: Most respondents rated the tool and the clarity of its content as excellent. The modules considered most relevant were those related to solving problems with future implications. The students considered the advice very applicable to everyday life and a good correspondence between problem situations and real life. Conclusion: This type of intervention is configured as one more option in the list of strategies to promote nursing students’ mental health, although it does not replace face-to-face care.